PERTAMINA IMAGE IMPROVEMENT STRATEGY IN CILACAP REFINERY TANK FIRE - Brasto Galih Nugroho; Dian Kuswardani (SEAN Institute, 2022)
Fuel tank 36 T-120 of Refinery Unit (RU) Cilacap PT Kilang Pertamina Internasional (PT KPI) was burned on Saturday, November 13, 2021. This incident happened all of sudden and unexpected because of thunder strike conjecture (natural factor). Crisis communication was handled to decrease the impacts and repair image. This research used a case study with in-depth interviews, participant observation, and secondary data as data collection methods. PT KPI was not alone at handling the crisis because PT KPI collaborated with local government, local police, and local military. Among five image repair strategies by William Benoit, PT KPI used reducing the offensiveness of the event, mortification, and corrective action strategies. Communication crisis handling of that incident can be seen as best practice when handling crisis caused by natural factors.